Analisis Teknik Pengambilan Gambar One Shot Dalam Memvisualisasikan Perubahan Karakter Pada Film “Sabda Kekasih” Sutradara Azhari Zain - Dwi Putri Mawar; Dani Manesah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
The one shot shooting technique for showing character changes in the main character in the film Sabda Kekasih is packaged very interestingly. This research was conducted with the aim of analyzing the one shot shooting technique used to show character changes in the main character. This research uses a descriptive qualitative method to reveal changes in the character of the main character which is displayed using the one shot technique. These character changes can be seen from the dialogue, expressions and behavior displayed and will be dissected using Lajos Egri's characterization theory which discusses the dimensions of physiology, sociology and psychology. The result of this research is that the character experiences a change in character due to an accident he experiences that makes him blind. So it can be concluded that the character changes that occurred to the main character in the film Sabda Kekasih occurred because of the accident he experienced.